Growth and reproductive performances of Hilly Brown Bengal goat under semi-intensive management condition at Naikhongchari hilly areas of Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2020)
The objective of the study was to evaluate the growth and reproductive performances of Hilly Brown Bengal (HBB) goats of different generations and conducted at Naikhongchari Regional Station Research Farm of Bangladesh Livestock Research Institute. Goats were reared in a plastic slated floor under semi-intensive system and were allowed to graze for 6-7 hours per day. Animals were given a concentrate mixture containing 17% CP, 11 MJ ME/kg DM provided twice daily in the morning and evening at the rate of 1% of their body weight. All goats were kept separately according to sex and age groups to avoid random mating. Natural mating program was performed to improve the economically important traits. Goats were de-wormed and diping on regular intervals and only PPR vaccine was given at the age of 2 months. Data on productive, reproductive and disease incidence of goat were recorded regularly and were analyzed. Results showed that Kid Birth Weight of HBB goats were significantly (P.05) effect on kid birth weight but significantly (p